Razvoj medicinskog turizma u Bosni i Hercegovini / Medical Tourism Development in Bosnia and Herzegovina - Čaušević, Amra (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Even though medical tourism is a modern concept, as a tourism practice it is not new. People have been always travelling for health reasons. Although there was still no international agreement on the definition and measurement regarding this trend has not been reached yet, its importance in the development of tourist destinations has begun to be taken into account. More recently, with the cutting-edge advancement in the treatment and health care delivery, the available and specialized medical treatments and medicines in use have increased over time. This paper explores and critically analyzes the issues of medical tourism in Bosnia and Herzegovina. As treatment costs increase in Western countries, the need for medical services in developing countries may increase. The paper will analyze the attractiveness of Bosnia and Herzegovina destinations with the aspect of medical tourism development. Medical tourism is sure to become more significant in the near future.